Spontaneous remission in three cases of AML M5 with NPM1 mutation. Issue 11 (21st October 2015) - Camus, Vincent; Etancelin, Pascaline; Jardin, Fabrice; Lenain, Pascal; Contentin, Nathalie; Daliphard, Sylvie; Buchonnet, Gérard; Lemasle, Emilie; Lanic, Hélène; Leprêtre, Stéphane; Penther, Dominique; Dubois, Sydney; et al.
Key Clinical Message: Patients with NPM1‐mutated AML M5 who develop spontaneous remission (SR) after antibiotic therapy at diagnosis seem to form a favorable prognosis and chemo sensitive subtype. We report three cases of AML M5 patients with the same genotype that experienced transient SR and are now leukemia free after standard treatment. Abstract : Patients with NPM1‐mutated AML M5 who develop spontaneous remission (SR) after antibiotic therapy at diagnosis seem to form a favorable prognosis and chemosensitive subtype. We report three cases of AML M5 patients with the same genotype that experienced transient SR and are now leukemia free after standard treatment.